Redesign business model of masjid kitchens as soup kitchens, providing jobs employment and nurturing of asnaf as entrepreneurs, and income generation for the masjid - Ahmad Dahlan, Abdul Rahman; Ibrahim, Jamaludin; Ahmad H. Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Mohamadali, Noor Azizah; Mahri, Nurhafizah; Abdul Aziz, Normaziah; Ismail, Amelia Ritahani; et al. (Pusat Islam UTM, 2021)
A survey conducted by the Department of Statistics Malaysia in May 2020 has found that: (a) 46.6% of self-employed respondents had reported losing their jobs; (b) an estimated 90% respondents were still working with lower than usual salaries; (c) more than two-thirds (71.4%) of self-employed respondents have sufficient financial savings for less than one month; and (d) the majority of respondents said they are unprepared if the duration of the MCO was extended except for employees under Government Linked Companies and multinational companies. In the “Families on The Edge” UNICEF report dated October 2020, COVID-19 crisis has pushed more low-income (or B40) urban Malaysian families into poverty. The poverty rate in the B40 community is higher than last year, with 50% of the families now living in absolute poverty. 70% of these households reported that COVID-19 had affected their ability to meet their basic living expenses, with 37% reporting that they struggle to purchase enough food for their families while 35% are unable to pay their bills on time. Hence, the main objectives of this paper is to offer a conceptual business model in turning masjid kitchens (or mKitchen) as a potential (a) soup kitchen for the B40 and Asnaf community, (b) job employment and nurturing of the Asnaf as entrepreneurs, and (c) income generation for the masjid via rental of kitchens. This is to turn the Asnaf community ‘Dari Penerima Zakat ke Pembayar Zakat’. The conceptual mKitchen business model can be adapted for possible implementation by masjid or mosques.